Bismuth sulfide particles, their manufacturing method and uses
By controlling the S/Bi molar ratio and heating bismuth sulfide particles, high blackness and specific reflectance properties are achieved, addressing the limitations of conventional particles for infrared and visible light applications.
Patent Information
- Application Number
- JP2021551363
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-09
- Filing Date
- 2020-09-30
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-09-30
AI Technical Summary
Conventional bismuth sulfide particles lack sufficient blackness and do not meet the desired reflectance properties for infrared and visible light, posing safety and environmental concerns due to hexavalent chromium in chromium oxide pigments.
The production of bismuth sulfide particles involves controlling the molar ratio of sulfur to bismuth (S/Bi) in an aqueous dispersion medium, followed by heating, to achieve high blackness and specific reflectance values at various wavelengths.
The resulting bismuth sulfide particles exhibit high blackness with reflectance values of 22.0 or less in the L*a*b* color system, with high infrared reflectance at 30.0% or more at 1200 nm and low visible light reflectance at 15.0% or less at 750 nm, suitable for infrared reflective and laser reflective materials.
Smart Images

Figure 0007606105000004 
Figure 0007606105000001 
Figure 0007606105000002
Abstract
Description
[Technical field]
[0001] The present invention relates to bismuth sulfide particles, a method for producing the same, and uses thereof, and in particular to an infrared reflective material containing the bismuth sulfide, a laser reflective material for LiDAR, a solvent composition, a resin composition, a coating composition, and a coating film containing the coating composition. [Background technology]
[0002] Many conventional black pigments contain chromium oxide, but during production, some of the chromium may change from trivalent to hexavalent, resulting in pigments containing hexavalent chromium. Pigments containing hexavalent chromium are designated as specific chemical substances, and there are concerns about their safety to the human body and the environment.
[0003] For this reason, the use of bismuth sulfide, which is not designated as a specified chemical substance, as a black pigment has been considered. For example, Patent Document 1 describes the use of bismuth sulfide particles as a black pigment in paints used for light absorbing materials and light-shielding films for liquid crystal displays. The bismuth sulfide particles are obtained by adding an aqueous solution of bismuth nitrate pentahydrate and sodium hydroxide dissolved therein, in which 3.3 moles of sodium thiosulfate are dissolved relative to the bismuth atoms, and heating the mixture while stirring.
[0004] In addition, Non-Patent Document 1 describes that black bismuth sulfide particles can be synthesized by adding nitric acid to an aqueous solution in which bismuth nitrate and thiourea in an amount 1.5 times the molar amount relative to the bismuth atoms are dissolved, and performing hydrothermal synthesis at a temperature of 180°C. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 5-264984 [Non-patent literature]
[0006] [Non-Patent Document 1] Materials Letters Vol.63(2009),pp.1496-1498 Summary of the Invention [Problem to be solved by the invention]
[0007] Bismuth sulfide particles produced by conventional methods are black in color, but the blackness is insufficient and does not have the desired blackness. [Means for solving the problem]
[0008] The present inventors conducted extensive research to obtain bismuth sulfide particles having a high blackness, and discovered that in the reaction between a bismuth compound and a sulfur compound, the compounding ratio of these compounds affects the blackness of the bismuth sulfide particles, and that bismuth sulfide particles with a higher blackness than conventional particles can be obtained, thereby completing the present invention.
[0009] That is, the present invention is as follows. [1] L * a * b * L of powder in color system * Bismuth sulfide particles having a value of 22.0 or less. [2] Bismuth sulfide particles according to [1], having a reflectance of 30.0% or more at a wavelength of 1,200 nm. [3] Bismuth sulfide particles according to [1] or [2], having a reflectance of 15.0% or less at a wavelength of 750 nm. [4] Bismuth sulfide particles according to any one of [1] to [3], having a reflectance at a wavelength of 1,550 nm of 50.0% or more. [5] An infrared reflective material comprising the bismuth sulfide particles according to any one of [1] to [4]. [6] A laser reflective material for LiDAR, comprising the bismuth sulfide particles according to any one of [1] to [4]. [7] A solvent composition comprising the bismuth sulfide particles according to any one of [1] to [4] and a solvent. [8] A resin composition comprising the bismuth sulfide particles according to any one of [1] to [4] and a resin. [9] A coating composition comprising the bismuth sulfide particles according to any one of [1] to [4] and a coating resin.
[10] A coating film comprising the coating composition described in [9].
[11] A method for producing bismuth sulfide particles, comprising the steps of mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi molar ratio) is 3.5 to 20, and then heating the mixture. Effect of the Invention
[0010] The bismuth sulfide particles of the present invention are * a * b * L in color space * It has a high blackness value of 22.0 or less. According to the present invention, for example, the following effects can also be obtained. The bismuth sulfide particles of the present invention can have a high infrared reflectance of 30.0% or more at a wavelength of 1200 nm. The bismuth sulfide particles of the present invention can be conveniently produced by mixing specific amounts of a bismuth compound and a sulfur compound in an aqueous dispersion medium, and then heating the mixture. [Brief description of the drawings]
[0011] [Figure 1] 1 is a reflectance spectrum of the powder of bismuth sulfide particles according to Example 1 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The bismuth sulfide particles of the present invention are a compound of bismuth and sulfur represented by the chemical formula Bi(III)2S3, etc., and are * a * b * L of powder in color system *The value of L is 22.0 or less, preferably 20.0 or less, more preferably 15.0 or less, and even more preferably 10.0 or less. * If the value is 0.01, the blackness of the bismuth sulfide particles is sufficiently high. * The value is the CIE 1976 Lab(L * a * b * The smaller the value, the lower the lightness. * The smaller the value, the higher the blackness (index of blackness). * The value can be measured by a color difference meter or the like, for example, RM-200QC portable color difference meter (product name) manufactured by X-rite can be used. In addition, “CIE 1976 Lab(L * a * b * "CIELAB" is a color space recommended by the CIE (International Commission on Illumination) in 1976, and is sometimes abbreviated as CIELAB.
[0013] In addition, the bismuth sulfide particles of the present invention are * a * b * Powder a in the color system * It is preferable that the value is -2.0 or more and 5.0 or less, and the b * It is preferable that the value is -3.0 or more and 8.0 or less. If it is in such a range, the bismuth sulfide particles of the present invention can have a black color with reduced redness, greenness, yellowness, and blueness. * Value, b * The value is L * a * b * It is an index that represents the hue and saturation of the color system. * The more positive the value, the more reddish the color, and the more negative the value, the more greenish the color. * The larger the value, the more yellowish it is, and the larger the value, the more blueish it is. * Value, b * For values, see L * The value can be measured in the same manner.
[0014] The bismuth sulfide particles of the present invention are * It is preferable that the reflectance at a wavelength of 1200 nm is 30.0% or more while maintaining the above reflectance value. The reflectance at this value is said to be sufficiently high for infrared rays. The reflectance is more preferably 35.0% or more, and even more preferably 40.0% or more. The infrared rays referred to here refer to electromagnetic waves with wavelengths of 780 nm to 2500 nm.
[0015] The reflectance here is the ratio of the radiant flux of light reflected back to the radiant flux of light irradiating the object. The reflectance can be measured by a spectrophotometer, for example, the UV-Visible Near-Infrared Spectrophotometer V-770 (product name) manufactured by JASCO Corporation.
[0016] In addition, the bismuth sulfide particles of the present invention preferably have a powder reflectance of 50.0% or more at a wavelength of 1550 nm, more preferably 60.0% or more, and most preferably 70.0% or more. If the reflectance is within the above range, the particles can also be suitably used as a laser reflecting material for Laser Imaging Detection and Ranging (LiDAR) using a wavelength of 1550 nm.
[0017] In addition, the bismuth sulfide particles of the present invention preferably have a powder reflectance of 15.0% or less at a wavelength of 750 nm, more preferably 13.0% or less, and most preferably 11.0% or less. If the reflectance is within such a range, visible light can be sufficiently absorbed, and the blackness of the powder is high. The visible light here refers to electromagnetic waves with a wavelength of 380 nm to 780 nm.
[0018] The BET specific surface area value (by nitrogen adsorption) of the bismuth sulfide particles of the present invention is 0.1 to 70 m 2 / g(0.1m 2 / g or more 70m 2 / g or less), and 1 to 40m 2 / g(1m 2 / g or more 40m 2 / g or less). Even more preferably, it is 1.4 to 37 m2 / g(1.4m 2 / g or more 37m 2 / g or less). From this BET specific surface area, the average particle diameter, assuming a spherical shape, can be calculated using the following formula 1. The average particle diameter calculated from this BET specific surface area is preferably 0.013 to 8.8 μm (0.013 μm or more and 8.8 μm or less), more preferably 0.02 to 0.88 μm (0.02 μm or more and 0.88 μm or less). Even more preferably, it is 0.023 to 0.63 μm (0.023 μm or more and 0.63 μm or less). Equation 1: L=6 / (ρ·S) where L is the average particle size (μm) and ρ is the density of bismuth sulfide (6.78 g / cm 3 ), S is the BET specific surface area of the sample (m 2 / g).
[0019] The powder pH of the bismuth sulfide particles of the present invention may be adjusted. The powder pH here refers to the pH of the aqueous solution after stirring the powder in pure water. The pH of the aqueous solution can be measured with a pH meter, for example, a pH meter D73 (product name) manufactured by Horiba, Ltd. Examples of methods for adjusting the powder pH include leaching treatment with an acid or alkali.
[0020] The present invention is a method for producing bismuth sulfide particles, which includes a step of mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi molar ratio) is 3.5 to 20, and then heating the mixture. Bismuth sulfide particles produced by a method including a step of mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi molar ratio) is 3.5 to 20, and then heating the mixture, is also one of the embodiments for carrying out the present invention. The heating temperature is preferably 30°C to 145°C.
[0021] The sulfur compound may be, for example, a thiocyanate such as potassium thiocyanate or sodium thiocyanate, a thiosulfate such as sodium thiosulfate, potassium thiosulfate or ammonium thiosulfate, or an organic sulfur compound such as thiourea. The sulfur compound may be either an anhydride or a hydrate. The sulfur compound is not limited to a powder form, and a mixed liquid obtained by mixing the powder with various solvents (water, formic acid, methanol, ethanol, 1-propanol, 2-propanol, etc.) may be used. The mixed liquid may be in a form in which the powder remains in the solvent, or in which the powder is dissolved in the solvent. A known acid or base may be added to dissolve the powder remaining in the solvent.
[0022] Examples of the bismuth compound that can be used include bismuth sulfate, bismuth nitrate, bismuth nitrate pentahydrate, bismuth subnitrate, bismuth hydroxide, bismuth oxide, bismuth chloride, bismuth bromide, bismuth iodide, bismuth oxychloride, bismuth subcarbonate, bismuth basic carbonate, etc. The bismuth compound is not limited to those in the form of powder, and a mixed liquid in which the powder is mixed with various solvents (water, formic acid, methanol, ethanol, 1-propanol, 2-propanol, etc.) can also be used.
[0023] The bismuth compound may be produced by a known method. For example, bismuth hydroxide can be produced as follows. Bismuth nitrate pentahydrate is mixed with nitric acid and heated. Sodium hydroxide is added thereto and the mixture is aged to obtain a mixture containing bismuth hydroxide. The obtained mixture is subjected to solid-liquid separation, and the solid content (bismuth hydroxide) is washed.
[0024] The aqueous dispersion medium is one whose main component is water, that is, one whose water content is 50% by mass or more. The water content in the aqueous dispersion medium is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass. Examples of components other than water include various organic solvents that dissolve in water (methanol, ethanol, isopropanol, butanol, acetone, methyl ethyl ketone, tetrahydrofuran, etc.), and it is particularly preferable to contain ethanol. The ethanol content in the aqueous dispersion medium is preferably 10% by mass or less. By containing an organic solvent, bismuth sulfide with a higher blackness can be produced.
[0025] The above raw materials may be mixed in any order. That is, the bismuth compound and the aqueous dispersion medium may be mixed in advance, and the sulfur compound may be added thereto, or the sulfur compound and the aqueous dispersion medium may be mixed in advance, and the bismuth compound may be added thereto. Alternatively, all the raw materials may be added to the aqueous dispersion medium at once and mixed.
[0026] In the raw material mixing step, the sulfur compound and the bismuth compound are mixed so that the S / Bi molar ratio is 3.5 or more and 20 or less. By setting the ratio in this range, bismuth sulfide particles with a higher blackness can be produced. The S / Bi molar ratio is preferably 5 or more and 12.5 or less, and more preferably 7.5 or more and 10 or less. The S / Bi molar ratio can be calculated by dividing the number of moles of sulfur atoms in the sulfur compound by the number of moles of bismuth atoms in the bismuth compound.
[0027] In the above-mentioned raw material mixing step, additives such as dispersants, emulsifiers, thickeners, antifoaming agents, surface conditioners, and anti-settling agents may be added as necessary.
[0028] The mixed solution obtained by the above mixing step is preferably adjusted in pH as appropriate depending on the raw materials used. For example, when bismuth hydroxide, sodium thiosulfate, and water are used as raw materials, the pH of the mixed solution obtained after the mixing step is preferably adjusted to 5 or less. More preferably, the pH is adjusted to 4 or less, and even more preferably, the pH is adjusted to 3 or less. There are no particular limitations on the pH adjuster, and known ones such as sulfuric acid, nitric acid, hydrochloric acid, sodium hydroxide, potassium hydroxide, etc. can be used. Note that the sulfuric acid used here is not included in the above-mentioned sulfur compounds.
[0029] The above raw materials can be mixed using a known mixer such as a stirrer, a mixer, a homogenizer, or an agitator.
[0030] The mixture obtained by the mixing step is heated to produce bismuth sulfide particles. The heating temperature is preferably 30° C. or higher, more preferably 30° C. or higher and 145° C. or lower, and bismuth sulfide with a higher blackness can be produced by heating at such a temperature. The heating temperature is more preferably 40° C. or higher and 120° C. or lower, and even more preferably 50° C. or higher and 90° C. or lower.
[0031] The heating time at the above temperature can be set arbitrarily, but is preferably 0.5 to 10 hours (0.5 hours or more and 10 hours or less).
[0032] After the heating step, the mixture may be evaporated to dryness or may be subjected to solid-liquid separation, if necessary. For solid-liquid separation, a known filtration method may be used, for example, a pressure filtration device such as a rotary press or a filter press, which is usually used industrially, or a vacuum filtration device such as a Nutsche filter or a Moore filter, etc. In addition, centrifugation or the like may also be used. In this case, washing with pure water or the like may be performed, if necessary.
[0033] The method may also include a step of drying the solid content obtained by the solid-liquid separation. When the method includes a drying step, the drying temperature and drying time can be set arbitrarily. For example, the drying temperature is preferably 30° C. or higher and 120° C. or lower, and the drying time is preferably 0.5 to 10 hours (0.5 hours or higher and 10 hours or lower). In the drying step, for example, a heating device such as a dryer, an oven, or an electric furnace can be used.
[0034] The bismuth sulfide particles produced by the above method may be subjected to appropriate particle size adjustment using a known pulverizer, classifier, or the like.
[0035] The bismuth sulfide particles produced by the above-mentioned method can be identified as bismuth sulfide by X-ray diffraction etc. For example, they can be identified based on a spectrum measured using an X-ray diffraction device Ultima IV (product name) manufactured by Rigaku Co., Ltd.
[0036] The bismuth sulfide particles of the present invention may have their particle surfaces coated with various inorganic compounds or organic compounds. Examples of inorganic compounds include metal oxides and / or metal hydrous oxides of silicon, aluminum, titanium, zirconium, tin, antimony, and the like. Examples of organic compounds include organic silicon compounds, organic metal compounds, polyol-based, amine-based, carboxylic acid-based organic compounds (specifically, trimethylolmethane, trimethylolethane, trimethylolpropane, pentaerythritol, dimethylethanolamine, triethanolamine, stearic acid, oleic acid, and salts thereof). The particle surfaces of bismuth sulfide may be coated with the inorganic compounds described above, and then further coated with the organic compounds described above. The amount of the inorganic compound or organic compound coated can be appropriately set.
[0037] As a method for coating the particle surface of the bismuth sulfide particles with an inorganic compound or an organic compound, a conventional surface treatment method such as titanium dioxide pigment can be used. Specifically, it is preferable to add an inorganic compound or an organic compound to a slurry of the bismuth sulfide particles to coat them, and it is more preferable to neutralize the inorganic compound or the organic compound in the slurry and deposit it to coat them. Alternatively, an inorganic compound or an organic compound may be added to and mixed with a powder of the bismuth sulfide particles to coat them.
[0038] The bismuth sulfide of the present invention may be subjected to a leaching treatment using an acid or alkali. Examples of the acid used for leaching include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, and hydrofluoric acid, and examples of the alkali include sodium hydroxide and potassium hydroxide.
[0039] The bismuth sulfide particles of the present invention can be used as a black pigment by utilizing the pigment properties thereof. In addition, the particles can be used as an infrared reflecting material by utilizing the infrared reflecting properties thereof. When used as an infrared reflecting material, the bismuth sulfide particles of the present invention may be used in combination with other colorants or infrared reflectors.
[0040] The bismuth sulfide particles of the present invention can also be suitably used as a laser reflecting material for Laser Imaging Detection and Ranging (LiDAR). For example, a laser having a wavelength of 1550 nm can be used for LiDAR, and the reflectance of the bismuth sulfide particles of the present invention at a wavelength of 1550 nm as shown in FIG. 1 is sufficient for use as a laser reflecting material for LiDAR.
[0041] The bismuth sulfide particles of the present invention and the infrared reflective material containing the same can be mixed with a solvent to form a dispersion or suspension (collectively referred to as a solvent composition). Examples of the solvent used for the dispersion or suspension include aqueous solvents, alcohols (methanol, butanol, ethylene glycol, etc.), esters (ethyl acetate, etc.), ethers, ketones (acetone, methyl ethyl ketone, etc.), aromatic hydrocarbons (toluene, xylene, mineral spirits, etc.), aliphatic hydrocarbons, and other non-aqueous solvents, or mixtures thereof. The dispersion or suspension may contain additives such as dispersants, emulsifiers, antifreeze agents, pH adjusters, thickeners, and antifoamers, as necessary. The concentration of bismuth sulfide in such a solvent composition can be appropriately set.
[0042] A known mixer can be used in the mixing step when preparing the above dispersion or suspension. In addition, degassing may be performed as necessary during the above mixing. Examples of mixers include a two-shaft mixer, a three-roll mill, a sand mill, etc. that are usually used industrially, and a homogenizer, a paint shaker, etc. can be used in the case of a laboratory scale. In this case, grinding media containing glass, alumina, zirconia, zirconium silicate, etc. may be used as necessary.
[0043] The bismuth sulfide particles of the present invention and the infrared reflective material containing the same can be mixed with a resin to form a resin composition. Examples of the resin used in the resin composition include, but are not limited to, the following:
[0044] Thermoplastic resins include: (1) General-purpose plastic resins (e.g., (a) polyolefin resins (polyethylene, polypropylene, etc.), (b) polyvinyl chloride resins, (c) acrylonitrile butadiene styrene resins, (d) polystyrene resins, (e) methacrylic resins, (f) polyvinylidene chloride resins, etc.), (2) Engineering plastic resins (for example, (a) polycarbonate resins, (b) polyethylene terephthalate resins, (c) polyamide resins, (d) polyacetal resins, (e) modified polyphenylene ethers, (f) fluororesins, etc.); (3) Super engineering plastic resins (e.g., (a) polyphenylene sulfide resin (PP), (b) polysulfone resin (PSF), (c) polyethersulfone resin (PES), (d) amorphous polyarylate resin (PAR), (e) liquid crystal polymer (LCP), (f) polyetheretherketone resin (PEEK), (g) polyamideimide resin (PAI), (h) polyetherimide resin (PEI), etc.) Examples are given below.
[0045] Examples of the thermosetting resin include (a) epoxy resin, (b) phenol resin, (c) unsaturated polyester resin, (d) polyurethane resin, (e) melamine resin, and (f) silicone resin.
[0046] Examples of thermoplastic elastomers include styrene-based, olefin / alkene-based, vinyl chloride-based, urethane-based, and amide-based elastomers.
[0047] In addition, the above resin composition may contain various additives, such as dispersants, emulsifiers, flame retardants, antifreeze agents, pH adjusters, thickeners, antifoamers, ultraviolet absorbers, antioxidants, etc. The concentration of bismuth sulfide in such a resin composition may be appropriately set, and a high-concentration master batch may also be produced.
[0048] In the step of mixing with the resin composition, the same method as in the mixing step in producing the dispersion or suspension can be used.
[0049] The bismuth sulfide particles of the present invention and the infrared reflective material containing the same can be mixed with a paint resin to form a paint composition. The paint resin is not particularly limited as long as it is generally used in paint applications, and can be, for example, various paint resins such as phenol resin, alkyd resin, acrylic alkyd resin, acrylic resin, acrylic emulsion resin, polyester resin, polyester urethane resin, polyether resin, polyolefin resin, polyurethane resin, acrylic urethane resin, epoxy resin, modified epoxy resin, silicone resin, acrylic silicone resin, fluororesin, ethylene vinyl acetate copolymer, acrylic-styrene copolymer, amino resin, methacrylic resin, polycarbonate resin, and polyvinyl chloride resin.
[0050] The above coating composition may contain various additives, solvents, etc., as necessary. Examples of additives include various commonly used dispersants, emulsifiers, antifreeze agents, pH adjusters, thickeners, defoamers, etc. Examples of solvents include water solvents, non-aqueous solvents such as alcohols (methanol, butanol, ethylene glycol, etc.), esters (ethyl acetate, etc.), ethers, ketones (acetone, methyl ethyl ketone, etc.), aromatic hydrocarbons (toluene, xylene, mineral spirits, etc.), and aliphatic hydrocarbons, or mixtures thereof. The concentration of bismuth sulfide in such coating compositions may be appropriately set.
[0051] In the step of mixing with the resin, the same method as in the mixing step in producing the dispersion or suspension can be used.
[0052] The above dispersion or suspension or the above coating composition can be applied to a substrate and cured to form a coating film, which can be used as a black coating film, an infrared shielding coating film, or even a heat insulating coating film.
[0053] The above dispersion or suspension or the above coating composition can be applied by any of the general methods, such as spin coating, spray coating, roller coating, dip coating, flow coating, knife coating, electrostatic coating, bar coating, die coating, brush coating, and a method of dropping droplets, without any restrictions. The tool used for applying the dispersion or suspension or coating composition can be appropriately selected from known tools, such as a spray gun, roller, brush, bar coater, doctor blade, etc. After application, the coating can be dried and cured to obtain a coating film. Baking may also be performed after drying. The baking conditions can be appropriately set, but for example, the baking time can be about 1 to 120 minutes in an oxidizing atmosphere at a temperature range of 40°C to 200°C. By setting these conditions, sufficient baking can be achieved in the drying furnace of the coil coating line.
[0054] Examples of substrates to which the dispersion, suspension or coating composition is applied include ceramic products, glass products, metal products, plastic products, paper products and the like.
[0055] The coating film can have the characteristics of the black pigment that the bismuth sulfide of the present invention has. For example, L * a * b * L of the coating in the color system * The value may be 10.0 or less, and preferably 7.0 or less.
[0056] The L of the above coating * When measuring the L value, for example, a paint composition with a pigment mass concentration (PWC) of 29.60% is prepared and applied to black-and-white chart paper using a bar coater with a wire number of 60 so that the dry coating film has a thickness of 67 μm to form a coating film. The coating film formed on the white background of the black-and-white chart paper is measured using a color difference meter. * Value, a * Value, b * As the color difference meter, for example, a product name RM-200QC manufactured by X-rite can be used.
[0057] Moreover, the coating film can have the infrared reflectance characteristic of the bismuth sulfide particles of the present invention. For example, the solar reflectance of the coating film at a wavelength of 780 to 2500 nm can be 20.0% or more, preferably 30.0% or more. Furthermore, since such a coating film has a certain degree of solar reflectance, it can suppress the temperature rise of the coating film surface compared to general black pigments.
[0058] When measuring the solar reflectance of a coating film at wavelengths of 780 to 2500 nm, for example, a coating composition with a pigment mass concentration (PWC) of 29.60% is prepared, and this is applied to black-and-white chart paper using a bar coater with a wire number of 60 so that the dried coating film has a thickness of 67 μm to form a coating film. The reflectance of the coating film formed on the white ground of the black-and-white chart paper at wavelengths of 780 to 2500 nm is measured using a spectrophotometer, and the solar reflectance at wavelengths of 780 to 2500 nm can be calculated using the method described in JIS K 5602. As the spectrophotometer, for example, an ultraviolet-visible-near infrared spectrophotometer V-770 (trade name) manufactured by JASCO Corporation can be used.
[0059] In addition, when measuring the surface temperature of a coating film, for example, a coating composition with a pigment mass concentration (PWC) of 29.60% is prepared and applied to black and white chart paper using a bar coater with a wire number of 60 so that the dried coating film has a thickness of 67 μm to form a coating film. The coating film formed on the white surface of the black and white chart paper is irradiated with infrared rays from above the coating film, and the temperature of the coating film surface after irradiation is measured. For example, an I-R type infrared light bulb (product name) manufactured by Iwasaki Electric Co., Ltd. can be used for infrared irradiation.
[0060] Furthermore, when the weather resistance of the above coating film was evaluated, it was found to have superior weather resistance to that of coating films using general black pigments.
[0061] The weather resistance can be evaluated by the time required for the color difference of the coating film before and after the exposure test to reach a predetermined value, and the longer the time required, the better the weather resistance. The exposure test referred to here is not particularly limited in terms of the method, and outdoor exposure tests and exposure tests using equipment for accelerated weather resistance tests can be used. Examples of equipment for accelerated weather resistance tests include a sunshine carbon arc lamp weather resistance tester (sunshine weather meter), a dew cycle weather resistance tester, an ultraviolet carbon arc lamp weather resistance tester, and a xenon arc lamp weather resistance tester.
[0062] When calculating the color difference of a coating film, for example, a coating composition with a pigment mass concentration (PWC) of 29.60% is prepared, and this is applied to a primer (zinc phosphate) treated steel plate using a bar coater with wire number 60 so that the dried coating film has a thickness of 67 μm, forming a coating film and preparing a test piece. The test piece is subjected to an exposure test using a sunshine weather meter, and the coating film after the exposure test is measured using a colorimeter to measure the L * Value, a * Value, b * The value was measured, and the color difference was calculated by the method described in JIS K 5600. As the sunshine weather meter, for example, S80 (product name) manufactured by Suga Test Instruments Co., Ltd. can be used, and as the colorimeter, for example, a spectrophotometer SD5000 (product name) manufactured by Nippon Denshoku Industries Co., Ltd. can be used. EXAMPLES
[0063] Examples of the present invention will be described below, but the present invention is not limited to these examples.
[0064] <L * a * b * L of powder in color system * Value, a * Value, b * How to measure values> After thoroughly crushing the sample in an agate mortar, the sample is placed in an aluminum ring of 20 mm diameter, and a load of 30 MPa is applied to press mold the sample. The sample is then measured using a portable color difference meter manufactured by X-rite (trade name: RM-200QC).
[0065] <Measurement of powder reflectance> After thoroughly grinding the sample in an agate mortar, the sample was placed in a measurement cell (powder cell PSH-002, manufactured by JASCO Corporation) to prepare a measurement sample. The measurement sample was attached to an integrating sphere unit (ISN-923, manufactured by JASCO Corporation), and the reflectance at wavelengths of 300 to 2500 nm was measured using an ultraviolet-visible-near infrared spectrophotometer (product name V-770, manufactured by JASCO Corporation).
[0066] <Measurement of powder pH> 1.0 g of the sample was weighed into a 200 mL beaker, 100 mL of pure water was added thereto, and ultrasonic dispersion was carried out for 5 minutes. Thereafter, the pH of the aqueous solution was measured using a pH meter (pH meter D73 (product name) manufactured by Horiba, Ltd.).
[0067] <Measurement of powder X-ray diffraction spectrum> After thoroughly grinding the sample in an agate mortar, the sample is placed in a measurement cell and measured using a horizontal multipurpose X-ray diffraction instrument, Ultima IV (product name), manufactured by Rigaku Co., Ltd. The obtained spectrum is collated with ICSD (Inorganic Crystal Structure Database) provided by the Chemical Information Association to identify the sample. The spectrum is collected under the following measurement conditions. (1)Optical system (A) Divergence slit 1° (a) Scattering slit 1° (c) Receiving slit 0.15mm (d) Monochrome receiving slit 0.8 mm (2)X-ray (A) Wavelength: CuKα 1.541Å (a) Tube current: 50mA (c) Tube voltage: 50kV (3) Measurement range: 5~70deg. (4) Scanning method (a) Scan speed: 5° / min (a) Step width: 0.02 deg.
[0068] <Preparation of bismuth hydroxide> 116.8 g of 60% nitric acid (manufactured by Nacalai Tesque, Inc.) was added to 277.6 g of pure water, and 146.1 g of bismuth nitrate pentahydrate (manufactured by Kanto Chemical Co., Ltd.) was further added thereto and mixed. 1459.5 g of pure water was added to this mixture to prepare a bismuth nitrate mixed solution. The bismuth nitrate mixed solution and a 3N sodium hydroxide aqueous solution were added to 4 L of pure water heated to 70°C while maintaining the pH at 6.5 to 7.5, and then aged for 10 minutes to obtain a mixed solution containing bismuth hydroxide, which was subjected to solid-liquid separation by suction filtration, washed with pure water, and the bismuth hydroxide was recovered.
[0069] <Preparation of bismuth sulfide> Example 1 The bismuth hydroxide obtained above was mixed with pure water to a concentration of 0.08 mol / L to prepare a 3.45 L slurry. In addition, pure water was added to sodium thiosulfate (manufactured by Nacalai Tesque, Inc.) to a concentration of 0.68 mol / L to prepare 1.98 L of sodium thiosulfate mixed solution. Next, the sodium thiosulfate mixed solution was added to the bismuth hydroxide slurry. The S / Bi molar ratio in this blend amount was 10. 150 g of nitric acid diluted to a concentration of 30% was added thereto. The pH of the mixed solution after the addition of nitric acid was 1.8. The obtained mixed solution was heated to 70°C and stirred for 2 hours to obtain a black precipitate in the mixed solution. The black precipitate was collected by suction filtration, washed with pure water, and dried at 100°C for 3 hours to obtain sample 1 of Example 1. For the obtained sample 1, a * value and b * The values were measured and * =0.1, b * =-0.4. In addition, the powder pH was measured and found to be 3.2.
[0070] Example 2 Sample 2 was obtained in the same manner as in Example 1, except that the S / Bi molar ratio in Example 1 was changed to 5. * value and b * The values were measured and * =0.1, b * =1.2.
[0071] Example 3 Sample 3 was obtained in the same manner as in Example 1, except that the S / Bi molar ratio was changed to 7.5. * value and b * The values were measured and * =0.2, b * =-1.0.
[0072] Example 4 Sample 4 was obtained in the same manner as in Example 1, except that the S / Bi molar ratio in Example 1 was changed to 15. * value and b * The values were measured and * =0.0, b * =2.9.
[0073] Example 5 Sample 5 was obtained in the same manner as in Example 1, except that the heating temperature was changed to 30° C. * value and b * The values were measured and * = 1.8, b * =4.2.
[0074] Example 6 Sample 6 was obtained in the same manner as in Example 1, except that the heating temperature was changed to 90° C. * value and b * The values were measured and * =0.2, b * =0.2.
[0075] Example 7 Sample 7 was obtained in the same manner as in Example 1, except that the heating temperature was changed to 120° C. * value and b * The values were measured and * =-0.1, b * =0.8.
[0076] Example 8 Sample 8 was obtained in the same manner as in Example 1, except that bismuth hydroxide was changed to bismuth nitrate pentahydrate (manufactured by Kanto Chemical Co., Ltd.) and the pH adjuster added after the raw material mixing step was changed to sodium hydroxide. The pH of the aqueous solution after the addition of sodium hydroxide was 4.9. * value and b * The values were measured and * =-0.3, b * =1.5.
[0077] Example 9 The black precipitate obtained in the same manner as in Example 1 was washed with pure water, and then, without drying, pure water was added so that the concentration of the black precipitate became 50 g / L, and the mixture was stirred to obtain a slurry. The slurry was transferred to a beaker, heated to 70° C., and 2.0% by mass of sodium aluminate calculated as Al2O3 was added to the black precipitate over 20 minutes while stirring well. After the addition, the pH of the slurry was adjusted to 7.0 using 20% by mass of sulfuric acid. Then, the mixture was stirred for 1 hour. The obtained slurry was filtered, washed, and dried at 100° C. for 3 hours to obtain Sample 9 of Example 9.
[0078] Example 10 The black precipitate obtained in the same manner as in Example 1 was washed with pure water, and then, without drying, pure water was added so that the concentration of the black precipitate became 50 g / L, and the mixture was stirred to obtain a slurry. The slurry was transferred to a beaker, and a 3N aqueous solution of sodium hydroxide was added to adjust the pH of the slurry to 6.5 to 7.5. The mixture was then heated to 70°C, and stirred for 2 hours while maintaining the temperature. The obtained slurry was filtered, washed, and dried at 100°C for 3 hours to obtain Sample 10 of Example 10. The powder pH of Sample 10 was measured to be 3.9.
[0079] Comparative Example 1 The experiment was carried out according to Example 1 of JP-A-5-264984. 3.33 g of bismuth nitrate pentahydrate and 0.72 g of sodium hydroxide were mixed in 34.3 ml of pure water. 2.70 g of sodium thiosulfate pentahydrate was mixed in 27.7 ml of pure water. The latter mixture was added to the former mixture, and heated at 95° C. for 20 hours while stirring, to obtain a precipitate in the mixture. The precipitate was collected by suction filtration, washed with pure water, and dried at 100° C. for 3 hours to obtain Sample 11 of Comparative Example 1. The S / Bi molar ratio was 3.3.
[0080] Samples 1 to 8, 11 products, powder L * The values and the reflectance of the powder are shown in Table 1. The reflectance spectrum of the powder of Sample 1 is shown in FIG.
[0081] [Table 1]
[0082] It was confirmed from the XRD spectrum that Samples 1 to 8 were Bi2S3. Sample 11 had a broad peak and could not be identified.
[0083] From Table 1, for the samples (samples 1 to 7) produced with S / Bi molar ratios of 3.5 to 20, the L * On the other hand, when the S / Bi molar ratio is out of the above range, the L * The value is greater than 22.0, and it is clear that the blackness is not sufficient.
[0084] In addition, the powder L of the sample (sample 8) in which the raw bismuth source was changed to bismuth nitrate was also * The value was 22.0 or less, and it was found that the blackness was sufficient.
[0085] Furthermore, all of Samples 1 to 8 have sufficient blackness, but the reflectance at a wavelength of 1200 nm is 30.0% or more, indicating high infrared reflectance characteristics. Also, the reflectance at a wavelength of 1550 nm is 50.0% or more, indicating high infrared reflectance characteristics. Also, the reflectance at a wavelength of 750 nm is 15.0% or less, indicating low visible light reflectance.
[0086] <Evaluation of coating film properties> Using Sample 1, Sample 9, or Sample 10, which had sufficient black infrared reflective properties, a coating composition and a coating film were prepared as follows, and the L * The value and the solar reflectance at wavelengths of 780 to 2500 nm were measured. As a reference example, a commercially available carbon black (product name MA-100: manufactured by Mitsubishi Chemical Corporation) was used.
[0087] <Preparation of coating composition> Using Sample 1, Sample 9, or Sample 10, a coating composition was prepared at a pigment mass concentration (PWC) of 29.60%. Specifically, each raw material was placed in a 100 ml mayonnaise bottle according to Table 2, and stirred with a stirrer (product name SM-101: manufactured by AS ONE Corporation) to prepare a mill base. Next, 15.6 g of an alkyd resin (Alkydia (registered trademark) J-524-IM-60: manufactured by DIC Corporation) was added to the mill base, and stirred with a stirrer (product name SM-101: manufactured by AS ONE Corporation) to obtain a coating composition.
[0088] [Table 2]
[0089] <Preparation of coating composition using carbon black (reference example)> A coating composition was prepared with a pigment volume concentration (PVC) of 5.8% using commercially available carbon black (product name MA-100: manufactured by Mitsubishi Chemical Corporation). Specifically, each raw material was placed in a 100 ml mayonnaise bottle according to Table 3, and dispersed using a paint conditioner (manufactured by Red Devil Co., Ltd.) to prepare a mill base. Next, 20.0 g of an alkyd resin (Alkydia (registered trademark) J-524-IM-60: manufactured by DIC Corporation) was added to the mill base, and dispersed using a paint conditioner (manufactured by Red Devil Co., Ltd.) to obtain a coating composition.
[0090] [Table 3]
[0091] <Preparation of coating film> Sample 1, Sample 9, Sample 10, or a commercially available carbon black coating composition was applied to a hiding power test paper (JIS-compliant product: manufactured by Motofuji) using a bar coater with wire number 60. This was left to stand for 30 minutes, and then dried at 110°C for 40 minutes using a dryer (product name DRM-620DA: manufactured by Advantec) to produce a coating film with a dried film thickness of 67 μm.
[0092] <L of coating film * Value Measurement> The above coating film was measured using a portable color difference meter (product name RM-200QC: manufactured by X-rite) * a * b * L in color space * Value (L on white background * values) were measured.
[0093] <Measurement of solar reflectance of coating film> The coating film was attached to an integrating sphere unit (manufactured by JASCO Corporation, product name ISN-923 type) and the reflectance (reflectance on a white background) at wavelengths of 780 to 2500 nm was measured using an ultraviolet-visible-near infrared spectrophotometer V-770 (product name) also manufactured by JASCO Corporation. The measured data was calculated using the weighting coefficients specified in JIS K 5602 to calculate the solar reflectance of the coating film at wavelengths of 780 to 2500 nm.
[0094] L of the coating using sample 1 * The value was 6.6, and the solar reflectance of the coating film in the wavelength range of 780 to 2500 nm was 38.4%.
[0095] L of the coating using sample 9 * The value was 5.9, and the solar reflectance of the coating film in the wavelength range of 780 to 2500 nm was 38.9%.
[0096] L of the coating using sample 10 * The value was 5.0, and the solar reflectance of the coating film in the wavelength range of 780 to 2500 nm was 38.7%.
[0097] Each coating using sample 1, sample 9, or sample 10 was * The value is 10.0 or less, which shows that the blackness is generally required for black coating films.
[0098] Moreover, each of the coating films using sample 1, sample 9, and sample 10 has a solar reflectance of 20.0% or more, and is therefore found to have the infrared reflectance characteristics generally required of an infrared reflective coating film.
[0099] The coating film using commercially available carbon black has a solar reflectance of 3.97%, which is lower than that of the coating film using the bismuth sulfide particles of the present invention, and it is clear that the coating film does not have the infrared reflectance properties generally required for an infrared reflective coating film.
[0100] <Evaluation of coating temperature> Using sample 1 and commercially available carbon black, a coating composition and a coating film were prepared as described above, and the surface temperature of the coating film after infrared irradiation was measured.
[0101] <Measurement of coating surface temperature> The coating film was cut into a 75 mm square and irradiated with an infrared lamp (Iwasaki Electric Co., Ltd., 250 W, Eye R type infrared lamp (product name)) from a position 400 mm above the coating film surface for 20 minutes, and the coating film surface temperature was measured.
[0102] The surface temperature of the coating film using Sample 1 after infrared irradiation was 59°C.
[0103] The surface temperature of the coating film using commercially available carbon black after infrared irradiation was 78° C., and it is clear that the surface temperature of the coating film using bismuth sulfide of the present invention was lower.
[0104] <Weatherability evaluation of coating film> Using Sample 1 or commercially available carbon black, coating compositions and coating films were prepared as described above, and the weather resistance of the coating films was evaluated. The time until the color difference of the coating film before and after the exposure test reached 5 or more was measured.
[0105] <Preparation of test specimens for exposure tests> Sample 1 or a commercially available carbon black coating composition was applied to a primer (zinc phosphate) treated steel plate using a bar coater so that the dry film thickness was approximately 67 μm, and then baked at 110°C for 40 minutes to prepare a test specimen.
[0106] <Calculation of the color difference of the coating film before and after the exposure test> The above test pieces were subjected to accelerated exposure by spraying water at regular intervals while irradiating light using a Sunshine Weather Meter (Suga Test Instruments Co., Ltd., product name S80). Color measurements were performed at regular intervals using a colorimeter (Nippon Denshoku Industries Co., Ltd., spectrophotometer product name SD5000), and the color difference was calculated according to a method in accordance with JIS K 5600.
[0107] The coating film using Sample 1 required 600 hours for the color difference before and after the exposure test to reach 5 or more, demonstrating its good weather resistance.
[0108] For the coating using commercially available carbon black, it took 180 hours for the color difference before and after the exposure test to reach 5 or more. [Industrial Applicability]
[0109] The bismuth sulfide particles of the present invention are * a * b * L in color space * Since the bismuth sulfide particles of the present invention have a high blackness value of 22.0 or less, they are useful as a black pigment. Moreover, since the bismuth sulfide particles of the present invention have a high infrared reflectance of 30.0% or more at a wavelength of 1200 nm, they are useful as an infrared reflective material.
Claims
1. L * a * b * Powder L in the color system * Bismuth sulfide particles having a value of 22.0 or less.
2. 2. The bismuth sulfide particle according to claim 1, which has a reflectance of 30.0% or more at a wavelength of 1,200 nm.
3. 3. The bismuth sulfide particle according to claim 1, which has a reflectance of 15.0% or less at a wavelength of 750 nm.
4. 4. The bismuth sulfide particle according to claim 1, which has a reflectance of 50.0% or more at a wavelength of 1,550 nm.
5. An infrared reflective material comprising bismuth sulfide particles according to any one of claims 1 to 4.
6. A laser reflective material for LiDAR comprising the bismuth sulfide particles according to any one of claims 1 to 4.
7. A solvent composition comprising the bismuth sulfide particles according to any one of claims 1 to 4 and a solvent.
8. A resin composition comprising the bismuth sulfide particles according to any one of claims 1 to 4 and a resin.
9. A coating composition comprising the bismuth sulfide particles according to any one of claims 1 to 4 and a coating resin.
10. A coating comprising the coating composition of claim 9.
11. A method for producing bismuth sulfide particles, comprising the steps of mixing a bismuth compound and a sulfur compound in an aqueous dispersion medium so that the ratio of the number of moles of sulfur atoms to the number of moles of bismuth atoms (S / Bi molar ratio) is 3.5 to 20, and then heating the mixture at 30° C. or more and 120° C. or less.
Citation Information
Patent Citations
Multilevel structure bismuth sulfide, preparation method and application thereof
CN104226335A
Water-phase preparation method of near-infrared photothermal nanomaterial bismuth sulfide
CN107098387A
One-step process of preparing monodispersive nanometer bismuth sulfide particle
CN1974406A
Light-absorbing materials for liquid crystal displays, light shielding films and liquid crystal display panels
JP1993264984A
